Improving the public-private-partnership system in Mongolia - BANZRAGCH, Undrakh (KDI School, 2018)
The concept of a Public-Private-Partnership (PPP) is an attractive, yet ambiguous one. It is a mechanism that has been widely welcomed and used to address huge infrastructure gaps and to reduce excessive government roles in public infrastructure development and provision in Mongolia. However, issues related to qualities of PPPs, fiscal problems, corruption, social disapprovals, manipulation - i.e. unknown risks - that are harmful to the society, have started to come up after 7 years of experience of actively promoting the PPP system. This paper based on empirical and comparative analyses, discusses that, the main causes of failures of PPPs have been that: 1) the flexibility and ambiguity of the PPP concept is not balanced against its accountability and efficiency; 2) that there is a lack of political will to nurture genuine partnership and a lack in the capability of the public sector; and 3) an uncompetitive private sector and immature environment. These factors have together created the maneuvering space for the manipulation of the PPP concept, its types, applicable infrastructures, institution as well as combined to promote fake procurement, management, economic analysis of PPPs, tendering, in general artificially legitimizing distorted partnerships in Mongolia. These distortions have enabled PPPs to be used in a socio-economically unbalanced way and have influenced the promotion of PPPs in an inefficiently allocative way at the expense of public interest. To eliminate confusions, instabilities and opportunisms within the PPP system, the paper proposes several must-implement policy recommendations by comparing the failure factors of Mongolian PPPs with success factors of the Republic of Korean PPPs. These are: to clarify all the existing confusions, to promote the check and balance mechanisms along with a fiscal safeguarding measures of various budget ceilings approaches, to enhance the accountability mechanism that is based on performance indicators for both public and private sectors as well as to shift from the ‘artificial’ PPPs procurement practice to the ‘proper’ and competitive procurement practice by taking various state-led deliberate measures. The paper concludes that if Mongolia could not take at least these must-implement measures, the PPP system might more harm the public interest than benefit it, due to the nature of infrastructure PPPs that are prone to rents.
Thesis(Master) --KDI School:Master of Public Policy,2018